Bioinformatics analysis and experimental verification of TIGD1 in non-small cell lung cancer - Xia, Lingchun; Yang, Zhuofan; Xv, Mingming; Wang, Guohui; Mao, Yaxin; Yang, Yihan; Tang, Jian (Frontiers in Medicine, 2024)
Non-small cell lung cancer (NSCLC) ranks as a prevalent form of respiratory system tumor. The human-specific gene, Triggered transposable element derivative 1 (TIGD1), exhibits marked overexpression in various tumor cells and tissues. Its vital involvement in the proliferation, invasion, and migration of cancer cells has been established through bioinformatics techniques. Both bioinformatics analysis and empirical studies have been utilized to validate the role of TIGD1 in NSCLC. We collected clinical data and gene expression profiles of lung adenocarcinoma from TCGA, UCSC XENA, and GEO databases. We used programming languages to process data and analyze the clinical characteristics, immune microenvironment, tumor mutation burden, and drug sensitivity of TIGD1. Furthermore, the role of TIGD1 in cellular processes was explored within the H1299 cell line. This was achieved using various methods including RNA interference, the CCK-8 assay, quantitative real-time PCR, wound-healing assays, western blotting, and the plate clone formation assay. Through bioinformatics analysis, we have discovered that TIGD1 has the potential to be a valuable biomarker for diagnosing and predicting lung cancer. Moreover, it shows promise as a target for immune-related therapy and targeted drug therapy. Furthermore, our study presents evidence of a potential association between the functional role of TIGD1 and its regulatory impact on the PI3K/AKT signaling pathway.